2016
DOI: 10.1021/acsnano.6b06361
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Nanoprobes for Stimulated Emission Depletion Nanoscopy

Abstract: Plasmonic nanoparticles influence the absorption and emission processes of nearby emitters due to local enhancements of the illuminating radiation and the photonic density of states. Here, we use the plasmon resonance of metal nanoparticles in order to enhance the stimulated depletion of excited molecules for super-resolved nanoscopy. We demonstrate stimulated emission depletion (STED) nanoscopy with gold nanorods with a long axis of only 26 nm and a width of 8 nm that provide an enhancement of up to 50% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 53 publications
(124 reference statements)
1
42
0
Order By: Relevance
“…Urban et al reported STED microscopy with 20 nm gold nanospheres coated with fluorescent silica and achieved approximately half the intensity of conventional STED based on dyes alone . Similar result was also obtained in gold nanorods reported by Cortes et al Although the methods reported above were beneficial for improving the resolution of STED nanoscopy, the required STED laser power was still very high. Quite recently, super‐resolution imaging (∆ x ≈ 28 nm) with an extremely low‐intensity STED beam was achieved using upconversion nanoparticles (UCNPs) as probes due to their exceptionally high stimulated‐emission efficiency .…”
mentioning
confidence: 56%
“…Urban et al reported STED microscopy with 20 nm gold nanospheres coated with fluorescent silica and achieved approximately half the intensity of conventional STED based on dyes alone . Similar result was also obtained in gold nanorods reported by Cortes et al Although the methods reported above were beneficial for improving the resolution of STED nanoscopy, the required STED laser power was still very high. Quite recently, super‐resolution imaging (∆ x ≈ 28 nm) with an extremely low‐intensity STED beam was achieved using upconversion nanoparticles (UCNPs) as probes due to their exceptionally high stimulated‐emission efficiency .…”
mentioning
confidence: 56%
“…This near‐field enhancement yields high depletion efficiencies of attached dyes even with low power lasers, provided that the depletion wavelength is close to the plasmon peak . As a note of caution, heating and heat‐induced movement of the metallic NPs may pose a problem for STED nanoscopy at depletion powers above 2 MW/cm 2 …”
Section: Nanoparticles For Super‐resolution Fluorescence Microscopymentioning
confidence: 98%
“…Instead of increasing the number of fluorophores in a NP, Maier and co‐workers amplified their luminescence by using electromagnetic field enhancement effected by plasmonic metal NPs. Light can resonantly excite collective oscillations of conduction electrons at the surface (surface plasmons) of a metallic NPs, thereby causing a dramatic increase of the local electric field.…”
Section: Nanoparticles For Super‐resolution Fluorescence Microscopymentioning
confidence: 99%
“…microfluidics, electrochemistry 2 ) with components for fluorescence spectroscopy and imaging; spatial and temporal resolution across many orders of magnitude (e.g. super-resolution imaging, 3,4 dynamic tracking); multiparametric encoding of information in the form of intensity, wavelength, anisotropy, and lifetime; and potential to respond to physicochemical attributes of the local environment (e.g. temperature, 5 viscosity, 6 pH 7 ) and molecular interactions.…”
Section: Introductionmentioning
confidence: 99%